Preliminary evidence for the role of HTR2A variants in binge eating in young women - Koren, Rachel (2014)
OBJECTIVE: We examined the association between 15 single nucleotide polymorphisms (SNPs) in HTR2A and characteristics of disordered eating, including weight/shape concerns, binge eating (with or without loss of control) and compensatory behaviors (purging and non-purging). Whether a lifetime history of major depressive disorder (MDD) moderated or mediated this association was also investigated. METHOD: A sample of 1533 twin women of Caucasian descent that were part of the Missouri Adolescent Female Twin Study was used. Data were collected using self-report responses to a semi-structured interview. Logistic regression analyses were used to examine the association between weight/shape concerns, binge eating and compensatory behaviors and SNPs (where carriers of the minor allele were coded as 1). RESULTS: Two SNPs, rs6561333 and rs2296972, showed a protective influence against binge eating, with rs2296972 being significant at a trend level after application of the False Discovery Rate. The SNP was not associated with MDD nor did MDD moderate its putative relation with binge eating. DISCUSSION: Pending replication, our analyses provide preliminary evidence for intronic SNPs in HTR2A and their association with binge eating. Given the well-documented role of serotonergic dysfunction in eating psychopathology, this report warrants considerable further study.